Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Organisasi, Dengan Komitmen Organisasi Sebagai Variabel Intervening - Syamsudin; Hadi Sunaryo; Nur Hidayah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
In this era of development, change in the organization is a must. Organizations must innovate and stay up to date in accordance with the demands and needs of the times so that the predetermined performance program can be carried out properly. The purpose of this research is to find out how the influence of leadership style and organizational culture on organizational performance, with organizational commitment as a connecting variable. This study used a census or saturated sampling method with a sample of 59 respondents. The data analysis used is descriptive quantitative with the Partial Least Square (PLS) method using the 3.0 program. The results of the study show that leadership style and organizational culture have a positive and significant effect on organizational performance. In addition, leadership style and organizational culture also affect organizational commitment. Organizational commitment also has a positive and significant effect on organizational performance. In addition, organizational commitment also acts as a mediator mediating the positive and significant influence of leadership style and organizational culture on organizational performance.